Bioenkapsulasi Karotenoid pada Skeletonema costatum dan Artemia Terhadap Pertumbuhan Larva Nila Air Payau - Ernawati Ernawati; Hamsir Hamsir (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
The research aimed at knowing and determining the proper dosage of carotenoids to the treatment of Skeletonema costatum and artemia for growth rate of the brackish water larvae. This research used Complete Random Design (CRD) with 4 treatments of carotenoid dosage (0, 10, 15 and 20 mg/L of media water) and each three replications. Larvae brackish water were reared during 30 days in 50 L silinder plastic in 12 units equipped by filter system. Giving 300.000 ind/L Skeletonema costatum and 500.000 ind/L nauplius Artemia was frequency twice a day such as at 08.00 and 17.00 o’clock WITA. The result showed that the highest Skeletonema costatum carotenoid content like 55,47 ppm was in the treatment of 20 mg/L dosage, the highest artemia carotenoid content was 7,181 ppm was in the treatment of 20 mg/L dosage and the highest larvae tilapia of brackish water carotenoid content like 2,33 ppm was in the treatment of 15 mg/L dosage. The growth rate the highest 1,65 cm and 0,2483% each contained of 10 mg/L dosage. Dose of 10 – 15 mg/L carotenoids were able to be absorbed and converted into vitamin A by the larvae so as to increase of growth rate of larvae nila of barckhish water.